RESEARCHES ON THE TEACHING OF LITERATURE IN BRAZIL - Antunes, Benedito [UNESP] (Univ Estado Mato Grosso, 2020)
This paper presents the preliminary results of a study on research groups focusing the teaching of literature and literary education in Brazil. One tries first, as an initial phase of a broader research, to quantify such groups and to determine their distribution around the country, and then to describe their main characteristics, based on profiles and information found in the Directory of Research Groups of the National Research Council (CNPq). It is a preparatory phase meant for the analysis of their scientific production, which will allow us to trace the theoretical and methodological trends underlying the researches carried out on the teaching of literature. The main conclusion of that phase of the research shows the existence of a large number of research groups which consider the most varied features of the teaching of literature in all regions of Brazil.
Keywords: Teaching of literature; Literary Education; Research groups; Reader's background